Philosophy Of Religious Education Management At State Elementary School 002 Kuaro - Firmansyah, Ahmad; Wardhana, Kautsar Eka (NOVARA: Nusantara Innovation and Educational Technology, 2024)
This research explores the philosophy of religious educational management at State Elementary School 002 Kuaro. he primary focus is to comprehend the philosophical principles underlying the administration of religious aspects in the context of elementary education. The research methodology employed is qualitative, utilizing interview and observation techniques. The research subject is State Elementary School 002 Kuaro, one of the formal educational institutions under the auspices of the Education Agency of Kabupaten Paser, established in 1974, located at the village of Keluang Paser Jaya, Kuaro District, Paser Regency, East Kalimantan Province, Indonesia. This study centers its attention on the scope of educational management in the school, including curriculum management, facility and infrastructure management, as well as financial management. The research findings indicate that the philosophy of religious education management at State Elementary School 002 Kuaro reflects religious values integrated into daily policies and practices. This includes instilling habits and rituals as an implementation of the teachings. Students are accustomed to participating in collective prayers, reading the Quran, and performing Friday Dhuha prayers together in the school courtyard, among other practices. In the implementation of the philosophy of religious management at State Elementary School 002 Kuaro, there are still several challenges, especially related to the utilization of facility and infrastructure management and financial management, in its efforts to enhance the application of religious management philosophy in the school.